Experimentação problematizadora com materiais alternativos na formação continuada de professores - Flora, Eliane (2011)
In this work a study was conducted to investigate the importance of problematizing experimentation with alternative materials for continuous training of teachers of Basic Education in the area of natural sciences and their technologies, during a training course of Continuing Education offered by the Secretary of the State of São Paulo, Education Board of the Region of São Joaquim da Barra. The workshop with low-cost alternative materials aimed to facilitate the construction of the student's knowledge and also it was used to promote continuous training for teachers. This work was elaborated in order to understand its possible contributions to development of teaching and the possibility to its implementation as a tool for aid to teaching in the classroom.